(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Wheat (Triticum aestivum) belongs to the family Poaceae or gramineae and genus triticum (Peterson et al, 2006). It was grown in the fertile region of the east, but now cultivated worldwide. It played an important role of religious significance and was part of the sacred rituals of many cultures. Greek, Roman, Sumerian and Finnish mythology had gods and goddesses of wheat. This exceptionally nutritious grain is still considered to be sacred in some areas of China (Proceedings of International Workshop on the importance of Sacred natural sites for Biodiversity Conservation, 2003). Wheat was introduced in the late 15th century when Columbus came to the New World. While wheat was grown in the United States during the early colonial years, it was not until the late 19th century that wheat cultivation flourished, owing to the importation of an especially hardy strain of wheat known as Turkey red wheat, which was brought over by Russian immigrants who settled in Kansas. Earlier, it was just picked wild, wherever it happened to grow. Around 10,000 B.C., people began to grow wheat for food. Gradually people made the wheat easier to grow and eat, by choosing the seeds of the best plants for the next years planting. They learnt different ways of cooking the wheat. They made porridge (like oat-meal) which is easy to cook and other times they made bread, which is harder to cook and needs more fuel, but could be carried around and kept it better than porridge, and tastes better.